Does Climate Change Adaptation Improve Technical Efficiency of Rice Farming? Findings From Yogyakarta Province Indonesia - Priyanto, Moh. Wahyudi; Mulyo, Jangkung Handoyo; Irham, Irham; Perwitasari, Hani; Siregar, Abi Pratiwa (Jurnal Manajemen & Agribisnis, 2022)
Food security of the Indonesian population is threatened because climate change has the potential to reduce technical efficiency of rice production. To adapt and reduce these negative impacts, farmers implement climate change adaptation strategies. This study aims to determine how the effect of climate change adaptation on the technical efficiency of rice farming. Research data was collected through interviews with 112 rice farmers in Sleman Regency. We carried out two stages of analysis, namely stochastic frontier analysis to determine the production function and efficiency level, and tobit regression to determine the effect of adaptation strategy on technical efficiency. The findings indicate that most farmers use short-lived varieties and apply two types of adaptation strategies in one growing season. By increasing the number of adaptation strategies, the technical efficiency of rice farming will increase. These results have important policy implications for increasing the adoption of adaptation strategies by farmers. The government and farmers should collaborate to formulate adaptation strategy policies to provide farmers with a choice of adaptation strategies. Keywords: adaptation, agricultural development, climate change, rice farming, technical efficiency